New species of the hairy-eyed horse fly subgenera Scaptia (Myioscaptia) Mackerras, 1955 and Scaptia (Scaptia) Walker, 1850 (Diptera: Tabanidae) from Australia - Lessard, Bryan D.; Yeates, David K. (Zootaxa, 2013)
New material has accumulated in several Australian Museums since Mackerras’ extensive 1960’s revision of the austral horse fly genus Scaptia Walker 1850, including one new species of Scaptia (Scaptia) Walker, 1850 and two new species of Scaptia (Myioscaptia) Mackerras, 1955. The new species are Scaptia (Scaptia) aurinigra Lessard, sp. n. and Scaptia (Myioscaptia) collessi Lessard, sp. n. both from Queensland, and Scaptia (Myioscaptia) lambkinae Lessard, sp. n. from Western Australia. All new species are described and illustrated. Additionally, an updated key to species of Scaptia (My-ioscaptia) is provided and includes all eleven known species of the subgenus. One novel species significantly extends the known distribution of the genus over 700 km further NE into central Western Australia.